Peranan Mahkamah Syari'ah Dalam Melindungi Hak-Hak Umat Islam: Kajian Terhadap Bidang Kuasa Mahkamah Syariah di Indonesia dan Malaysia - Afriadi Bin Sanusi (Al-Risalah, 2010)
This paper compares the social role of shari'a courts in indonesia and malaysia. it pays paticular attention to wht extent the role of these shari'a courts in these countries enabble the court to protect religious rightsof muslims concerning consumption of halal food. this is comperative study using comperative analysis and comperative law framework.